Caffeine attenuates seizure and brain mitochondrial disruption induced by Tramadol: the role of adenosinergic pathway. (2nd November 2021) - Samadi, Mahedeh; Shaki, Fatemeh; Bameri, Behnaz; Fallah, Marjan; Ahangar, Nematollah; Mohammadi, Hamidreza
Abstract: Tramadol (TR) is an analgesic drug used to treat moderate-to-severe pain but it induces seizure even at therapeutic doses. The exact mechanism of TR-inducing seizure is not clear but inhibition of the serotonin, GABA, and nitrous oxide (NOS) pathways are the commonly proposed mechanisms. Adenosinergic system has a crucial function in the modulation of seizure. Also, oxidative damage is an unavoidable effect of the seizure. This study was conducted to evaluate the role of the adenosinergic system on the seizure and oxidative stress biomarkers induced by TR using antagonist of the adenosinergic receptors in the Albino mice. For that purpose, generated clonic seizure, as seizure threshold, was evaluated by TR. Caffeine (CAF; 8 mg/kg, i.p.), a nonselective antagonist of adenosine receptors, was administered 1 hour before the seizure induction. The seizure threshold significantly increased by CAF-treated group when compared to TR group ( p < 0.001). Oxidative stress biomarkers such as reactive oxygen species, protein carbonyl content, and lipid peroxidation significantly decreased and glutathione content significantly increased by CAF in brain mitochondria compared to the TR group, whereas oxidative biomarkers significantly increased in the TR group compared to the control group. The results of the present study suggested that the adenosinergic system is involved in seizure induced by TR and meanwhile, inhibition of adenosine receptors can decrease the TR seizure threshold and also decrease the induced oxidative damage in the brain mitochondria.